Արդի ֆրանսերենի համադրական և վերլուծական բաոամիավորների ոճական մի քանի առանձնահատկությունների մասին - Վարդուշ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
It is in the process of comparative analyses of synthetic and analytical word units that a number of semantic, stylistic and grammatical (mainly referring to aspect) features come to light. In the current article an attempt is made to reveal the stylistic peculiarities of analytical word units,which become more vivid in the comparison with synthetical verbs. Colloquial words and those peculiar to the national speech, also idiomatic phrases which carry expressive and emotional colouring make the main word stock of the colloquial language. These can form synonymic groups with stylistically neutral words and idiomatic phrases used in all styles of the language. They enrich the colloquial language and make it even lively and colourful.
Keywords: Language and Literature